Neuro-navegática: software desenvolvido para interação com Brain Computer Interface para auxiliar o processo de inclusão escolar de pessoas com paralisia cerebral - Regina de Oliveira Heidrich; Marsal Avila Alves Branco; João Batista Mossmann; Anderson Schuh (Universidade Estadual de Campinas, 2014)
A Brain-Computer Interface (BCI), allows a person to transfer commands to a computer directly. Instead of using a keyboard, mouse or other input device, the user of this interface simply sends commands via brain waves and the computer responds to them. This paper aims to present a game developed to assist the process of educational inclusion of people with cerebral palsy. Qualitative research approach. To develop this research, we chose the case study, because it is a multifaceted research, in depth, of a single social phenomenon. Development of the Game Neuro-Navegática, with different forms of scanning speed, the software allows the user through the blink of an eye to choose the subject. In this example we opted for mathematics. The study on Brain Computer Interface (BCI) seeks to improve the way of interaction between humans and machines and allows people with cerebral palsy to may be benefited in the inclusive education process as well as their peers without disabilities.